Optimization Of Laser Soldering Parameters On Passive Devices - Nazarudin, Muhammad Zaim Hanif (Universiti Sains Malaysia, 2021)
Laser soldering is a non-contact process that important in soldering technology for miniature components because it can emit a controlled heating from laser beam to a specific location of solder joint and this process also can prevent damaging other components on electronic devices. The process parameter of laser soldering also important to be known which is laser power, process time and shape of laser beam to produce a consistent soldering result. However, in this research study will focus on VOF model in ANSYS Fluent software because the process parameter of laser soldering has been given by Western Digital. The main goal of this study is to optimise the parameters that affect the effectiveness in laser soldering process on passive devices. The parameter which is solder volume and temperature can affect the formation of fillet shape, velocity, and pressure of solder. Numerical simulation has been conducted to identify the suitable solder volume of SAC305 and the process temperature that can affect in solder joint reliability such as void. Thus, the parameters in the soldering process needed to be controlled to produce a good quality, long lifespan, and more reliable solder joint. The results obtained from the simulation can be visualise the flow of SAC305 solder at the end of reflow process in contour of volume fraction and temperature. The visualisation results can show the details trajectory of solder as it undergoes the thermal reflow. Besides, good relation can be seen between the simulation results obtain and validation from IPC standard. The study of VOF model showed the usable of simulation approach to simulate the process of laser soldering that can produce a good results of solder joint.